Strategies to Improve the Outcome of Cryoballoon Ablation in the Treatment of Atrial Fibrillation - Huang, Ying (Biomed Res Int, 2020)
Atrial fibrillation (AF) is a common arrhythmia contributing to severe outcomes, including cardiac dysfunction and stroke, and it has drawn great attention around the world. Drug therapies have been available for many years to terminate AF and control heart rate. However, the results from clinical studies on drug therapies have been discouraging. Mounting evidence indicates that radiofrequency catheter ablation (RFCA) is a safe and effective method to maintain sinus rhythm, especially in patients who are drug intolerant or for whom the drugs are ineffective, although it is a technically demanding and complex procedure. Fortunately, a novel application, cryoballoon ablation (CBA), with outstanding characteristics has been widely used. Great outcomes based on CBA have manifested its significant role in the treatment of AF. However, how to improve the safety and efficacy of CBA is a question that has not been well-answered. Would it be helpful to develop a different generation of cryoballoon? Is bonus freezing beneficial, or not? Is it better to prolong freezing time? Dose CBA combined with RFCA bring higher success rates? In this review, we comprehensively summarized useful applications for improving outcomes of CBA in AF patients.